A bivalent vaccine containing D614G and BA.1 spike trimer proteins or a BA.1 spike trimer protein booster shows broad neutralizing immunity. Issue 9 (2nd June 2022) - Du, Peng; Li, Ning; Xiong, Xinxin; Tang, Shengjun; Dai, Qinjin; Liu, Zhihai; Wang, Taorui; Gu, Xueping; Zhou, Zhongcheng
Abstract: The newly emerged severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) Omicron variant, sublineages BA.1 and BA.2, recently became the dominant variants of concern (VOCs) with significantly higher transmissibility than any other variant appeared and markedly greater resistance to neutralization antibodies and original ancestral WA1 spike‐matched vaccine. Therefore, it is urgent to develop vaccines against VOCs like Omicron. Unlike the new booming messenger RNA (mRNA) vaccine, protein vaccines have been used for decades to protect people from various kinds of viral infections and have advantages with their inexpensive production protocols and their relative stability in comparison to the mRNA vaccine. Here, we show that sera from BA.1 spike protein vaccinated mice mainly elicited neutralizing antibodies against BA.1 itself. However, a booster with BA.1 spike protein or a bivalent vaccine composed of D614G and BA.1 spike protein‐induced not only potent neutralizing antibody response against D614G and BA.1 pseudovirus, but also against BA.2, other four SARS‐CoV‐2 VOCs (Alpha, Beta, Gamma, and Delta) and SARS‐CoV‐2‐related coronaviruses (pangolin CoV GD‐1 and bat CoV RsSHC014). The two recombinant spike protein vaccines method described here lay a foundation for future vaccine development for broad protection against pan‐sarbecovirus.